SLEad: Electronic Tongue Data Analysis System - Bergamo, Bruno Barreto; Garcia, Rogério Eduardo; Giacometti, José Alberto (INFOCOMP Journal of Computer Science, 2008)
It was developed an “electronic tongue” – Electronic Tongue System (ETS), in Portuguese Sistema de Língua Eletrônica (SLE) –, instrument employing an array of capacitive sensors. Experimental data collected from several sensors are analyzed by Principal Component Analysis (PCA) and Artificial Neural Networks (ANN) techniques using different tools that support each technique separately. This work aims mainly to describe a software tool to perform the data acquisition and the computational tasks involved in data analysis. Software modules were implemented for the PCA and ANN analysis and they were integrated to the SLE instrument. Results obtained here are compared to the ones obtained using other tools, such as WEKA and MatLab, in order to validate the software developed by us.